2022
DOI: 10.1007/s10508-022-02399-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Bidirectional Association Between Daily Sexual and Relationship Satisfaction That Is Moderated by Daily Stress

Abstract: Prior research provides mixed evidence regarding the direction of the association between sexual and marital satisfaction. Whereas some studies suggest a bidirectional association, other studies fail to document one direction or the other. The current investigation used a 12-day diary study of 287 married individuals to clarify the nature of this association. Results from time-lagged mixed modeling revealed a significant positive bidirectional association. Both higher global sexual satisfaction one day and sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…Partners’ feelings about their intimate relationships fluctuate in response to evolving circumstances, such as daily stress (Zhao et al, 2022) and financial strains (Masarik et al, 2016). Yet over the last decade, characterizations of marital satisfaction change have largely emphasized stability and steady declines (e.g., Bühler et al, 2021; Karney & Bradbury, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Partners’ feelings about their intimate relationships fluctuate in response to evolving circumstances, such as daily stress (Zhao et al, 2022) and financial strains (Masarik et al, 2016). Yet over the last decade, characterizations of marital satisfaction change have largely emphasized stability and steady declines (e.g., Bühler et al, 2021; Karney & Bradbury, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…There is suggestive evidence that relationship satisfaction does fluctuate, at least across short timescales. Diary studies reveal that satisfaction and commitment fluctuate in response to time-varying stress (Neff & Karney, 2009), sexual satisfaction (Birnbaum et al, 2006;Zhao et al, 2022), and financial strain (Gajos et al, 2022), with individuals who report lower levels of attachment security and trust (Campbell et al, 2005(Campbell et al, , 2010Campbell & Marshall, 2011;Cooper et al, 2018) and higher levels of stress (Zhao et al, 2022) showing greater volatility in their daily and weekly satisfaction ratings. Further, larger fluctuations in satisfaction and commitment have been related to depression (Whitton & Whisman, 2010) and relationship dissolution in dating couples (Arriaga, 2001), over and above initial levels and slopes.…”
Section: Theoretical and Empirical Investigations Of Relationship Dev...mentioning
confidence: 99%
“…First, while we examined the link between sexual and relationship satisfaction at yearly intervals, past longitudinal studies have used different time lags, spanning from two months (e.g., Vowels & Mark, 2020) to 8–10 years (e.g., Quinn-Nilas, 2020). Although the optimal time lags for studying relationship development remain underexamined (Karney & Bradbury, 2020), it could be possible that the link is more bidirectional in shorter time frames (Zhao et al, 2022), but one direction of effect lasts longer than the other over time. Future research using different time lags could be informative in delineating the extent to which the temporal effects of sexual and relationship satisfaction could vary over different time intervals.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies found that earlier sexual satisfaction predicted subsequent relationship satisfaction but not the reverse (Fallis et al, 2016; Yeh et al, 2006), others showed that earlier relationship satisfaction predicted subsequent sexual satisfaction but not the other way around (Vowels & Mark, 2020). Meanwhile, some studies also found support for bidirectional associations (McNulty et al, 2016; Quinn-Nilas, 2020; Zhao et al, 2022), whereas others found limited evidence for long-term associations in either direction (Byers, 2005; Sprecher, 2002).…”
Section: Overview Of Past Inconsistenciesmentioning
confidence: 99%
“…It seems unlikely that completing more household labor than usual would have any bearing on being more or less satisfied than is typical 1 year later unless the upward deviation in household labor reflects a longer term pattern. Indeed, amidst an increasing recognition that many aspects of couple relations tend to be relatively stable across the long-term (Anderson et al, 2010; Joiner et al, 2024; Proulx et al, 2017), scholars are increasingly interested in how short-term fluctuations in partnership dynamics are associated with fluctuations in quality (e.g., Gajos et al, 2022; Johnson et al, 2022; Zhao et al, 2022). To this aim, daily and weekly diary data have been valuable, but remain rare in studies about household labor (for an exception, see Gordon et al, 2022).…”
Section: Introductionmentioning
confidence: 99%